Evaluation of In Vitro Activity of the Class I PI3K Inhibitor Buparlisib (BKM120) in Pediatric Bone and Soft Tissue Sarcomas - Anderson, Jennifer L.; Park, Ann; Akiyama, Ryan; Tap, William D.; Denny, Christopher T.; Federman, Noah (PLOS ONE, 2015)
Pediatric bone and soft tissue sarcomas often display increased Akt phosphorylation through up regulation of insulin-like growth factor (IGF1) signaling. Additionally, Akt signaling has been linked to resistance to IGF1 receptor (IGF1R) and mTOR (mammalian target of rapamycin) inhibitors in sarcoma, further demonstrating the role of Akt in tumor survival. This suggests targeting components of the PI3K/Akt pathway may be an effective therapeutic strategy. Here, we investigated the in vitro activity of the pan-class I PI3K inhibitor buparlisib (BKM120) in pediatric bone and soft tissue sarcomas. Buparlisib inhibited activation of Akt and signaling molecules downstream of mTORC1 (mTOR complex 1) in Ewing sarcoma, osteosarcoma, and rhabdomyosarcoma cell lines. Anti-proliferative effects were observed in both anchorage dependent and independent conditions and apoptosis was induced within 24 hours of drug treatment. Buparlisib demonstrated cytotoxicity as a single agent, but was found to be more effective when used in combination. Synergy was observed when buparlisib was combined with the IGF1R inhibitor NVP-AEW541 and the mTORC1 inhibitor rapamycin. The addition of NVP-AEW541 also further reduced phospho-Akt levels and more potently induced apoptosis compared to buparlisib treatment alone. Additionally, the combination of buparlisib with the MEK1/2 inhibitor trametinib resulted in synergy in sarcoma cell lines possessing MAPK pathway mutations. Taken together, these data indicate buparlisib could be a novel therapy for the treatment of pediatric bone and soft tissue sarcomas.